Effects of Social Capital on Senior High School Student Educational Outcomes in the Greater Accra Region of Ghana - Amakye, E.K. (University of Ghana, 2023)
This dissertation examined the effect between social capital and educational outcomes among senior high school students in two distinct educational settings: Ada Senior High Technical School and Kwabenya Community Senior High School. The study explores the influence of three dimensions of social capital, namely family support, peer networks, and student-teacher relationships, on students' educational outcomes. Additionally, it investigates the differences in social capital and educational outcomes between boarding and day students. The study population was drawn from Ada Senior High Technical and Kwabenya Community Senior High School. The study made use of a 200-sample size drawn from the population. The study used a mixed-method research approach where questionnaires was administered and two focus group discussions one at Kwabenya Community Senior high School and Ada Senior high Technical School were used to collect data. The findings reveal a positive and significant relationship between social capital and educational outcomes in both schools, highlighting the crucial role of a supportive social environment in fostering student success. Family support, peer interactions, and student-teacher relationships were identified as influential factors that explain a substantial portion of the variation in academic achievements. The findings also reveal that boarding student consistently exhibit stronger effects of the various social capital on educational outcomes compared to the day students.
MA. Development Studies
Keywords: social capital; educational outcomes; senior high school; Ada Senior High Technical School; Kwabenya Community Senior High School